The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1038/bjc.1979.219
|View full text |Cite
|
Sign up to set email alerts
|

The spread of breast cancer: importance of the intrathoracic lymphatic route and its relevance to treatment

Abstract: Summary. Detailed necropsies were performed on 26 individuals who had died of disseminated breast carcinoma, to assess the frequency of spread to the lungs, pleura and pericardium, and to determine the likely routes of spread to these sites. Tumour was present in the lung parenchyma in 67% of the lungs examined, in the visceral pleura in 75%o and the parietal pleura in 5Oo0. Although even small deposits of pleural tumour were invariably visible to naked-eye examination, lung parenchymal involvement was almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 9 publications
(7 reference statements)
0
17
0
Order By: Relevance
“…16,17 Autopsy studies on breast cancers reported metastasis to the lung in 57-77% of cases. 14,15,18,19 A variety of thoracic metastasis patterns of breast cancers are recognized, 20 including pleural metastasis, mediastinal tumor, lymphangitic carcinoma, multiple pulmonary nodules, solitary pulmonary nodule, endobronchial metastasis, and pulmonary tumor emboli. 20 Among these metastatic patterns, a solitary lung metastatic nodule would likely mimic a primary lung cancer, and, therefore, may cause a significant diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Autopsy studies on breast cancers reported metastasis to the lung in 57-77% of cases. 14,15,18,19 A variety of thoracic metastasis patterns of breast cancers are recognized, 20 including pleural metastasis, mediastinal tumor, lymphangitic carcinoma, multiple pulmonary nodules, solitary pulmonary nodule, endobronchial metastasis, and pulmonary tumor emboli. 20 Among these metastatic patterns, a solitary lung metastatic nodule would likely mimic a primary lung cancer, and, therefore, may cause a significant diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Given that breast cancer is one of the known extrathoracic malignancies that metastasise to mediastinal nodes [3][4][5], this finding of a direct communication of breast lymphatic drainage with the intrapulmonary lymphatic system provides a potential mechanism for this pattern of spread. This case highlights how the combination of functional and anatomical information provided by SPECT/CT in lymphoscintigraphy continues to improve our understanding of potential paths of cancer spread.…”
mentioning
confidence: 99%
“…An autopsy series of women who died of disseminated breast cancer revealed metastatic involvement of intrathoracic LNs in 71% of cases. 25 The second most common site of distant metastasis is bone, and bone metastasis is detected in 31% of all patients with metastasis. 26 Radiologically, skeletal metastases could be either lytic or sclerotic lesions or a combination of both (Fig.…”
Section: Detection Of Distant Metastasis To Thoraxmentioning
confidence: 99%